2020
DOI: 10.4414/smw.2020.20253
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tuberculosis in migrant children in Switzerland and relevance of current screening guidelines

Abstract: AIMS: Since 2016, Swiss guidelines recommend screening of all migrant children <5 years of age for tuberculosis (TB) and to screen older children only if they have risk factors for tuberculosis. Our goals were to describe the epidemiology of latent tuberculosis in migrant children at the Lausanne University Hospital, to identify determinants of latent tuberculosis and tuberculosis disease, and to evaluate the risk of a false-positive tuberculin skin test when using a positivity limit of 5 mm. CONCLUSION: Scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…( Soriano-Arandes et al., 2020 ) Living conditions including poor housing, poverty, and urban environments are also associated with higher tuberculosis prevalence and transmission. ( Stosic et al., 2019 ; Bekken et al., 2020 ; Boukamel et al., 2020 ; Martinez et al., 2020 ) Unlike adult tuberculosis, there is no gender difference in childhood tuberculosis, ( Marais et al., 2004 ; Nelson and Wells, 2004 ; Swaminathan and Rekha, 2010 ) and in this study we did not find gender differences in either PTB or EPTB.…”
Section: Discussionsupporting
confidence: 53%
“…( Soriano-Arandes et al., 2020 ) Living conditions including poor housing, poverty, and urban environments are also associated with higher tuberculosis prevalence and transmission. ( Stosic et al., 2019 ; Bekken et al., 2020 ; Boukamel et al., 2020 ; Martinez et al., 2020 ) Unlike adult tuberculosis, there is no gender difference in childhood tuberculosis, ( Marais et al., 2004 ; Nelson and Wells, 2004 ; Swaminathan and Rekha, 2010 ) and in this study we did not find gender differences in either PTB or EPTB.…”
Section: Discussionsupporting
confidence: 53%
“…For example, one study observed that, among 200 migrant children, for protection against HBV, only 118 (59%) had anti-HBs ≥1000 UI/L compared to 23 (11%) having no detectable antibodies (<10 IU/L) [ 57 ]. Some serological studies also noted false-negative results; for instance, some non-tuberculosis patients had false-positive tuberculin skin tests despite being BCG-vaccinated [ 19 ]. Regardless of some variance in accuracy and specificity, serology served as an approximation of protection levels across different migrant groups [ 44 , 45 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies analyzing the impact of the most recent refugee crises on TB in Europe showed that up to 14% of unaccompanied minor refugees had TB infection when screened in Germany [13] and Sweden in 2015 [14]. A Swiss study in newly arrived migrant children shows 7% of screened children had TB infection or TB disease, and an association with origin from a country with moderate to high TB incidence, older age, and contact to a TB index case was found [15]. However, detailed data on incidence rates, associated risk factors, and clinical characteristics in children with TB after migration to Europe are important and lacking in most national and regional reports [16, 17].…”
Section: Introductionmentioning
confidence: 99%